Achievement motivation and its relationship to adaptive behavior among orphan and non-orphans students in the intermediate stage (Journal of the College of Basic Education, 2022)
The family is considered the first social body that is responsible for preparing the individual for the future of his life, and for carrying out his role in society, and which transmits to him the opinions, beliefs, values, and customs prevailing in that society, as his biological and psychological needs are satisfied through the mother in the first place, then the father, followed by The rest of the family members help him to adequately satisfy these needs through love and tenderness (Abdullah, 1980: 38). And if we look at the problems that families suffer from in all societies of the world in different forms and types, such as death, disintegration, dissolution, separation from the context of the normal family, and other problems that actually affect the destruction of the natural foundations of the family, we find that they are among the most dangerous factors that destroy the child’s personality socially, psychologically, culturally, and morally.